2017
DOI: 10.1039/c7fo00495h
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Potentilla anserina polysaccharide on cadmium-induced nephrotoxicity in vitro and in vivo

Abstract: The aim of this research was to investigate the antioxidant and anti-apoptotic activities of Potentilla anserina polysaccharide (PAP) on kidney damage induced by cadmium (Cd) in vitro and in vivo. PAP has been suggested to have anti-oxidation, anti-apoptosis, immunoregulation, antimicrobial, antitussive, and expectorant abilities. In this study, PAP was extracted and the major components of PAP were analyzed. It was shown that PAP pretreatment remarkably improved redox homeostasis, both in human embryonic kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Inhibition in the activities of SOD, CAT, GSH-Px, and GSH-R in the renal tissue of CdCl 2 -injected mice could be caused by the reduced synthesis of enzymes or oxidative inactivation of protein enzymes 22 . Our findings in this study were in agreement with other studies, which revealed that cadmium induced kidney toxicity by enhancing ROS formation, GSH consumption, and inhibiting antioxidant-mediated defense system 34 . However, this study also suggested that the pre-administration of RJ prior to cadmium injection prevented the alteration in enzymatic and non-enzymatic activity of antioxidant molecules, and the antioxidant and metal-chelating properties of RJ also prevented the generation of free radicals, further reducing the cadmium-induced oxidative damage.…”
Section: Discussionsupporting
confidence: 93%
“…Inhibition in the activities of SOD, CAT, GSH-Px, and GSH-R in the renal tissue of CdCl 2 -injected mice could be caused by the reduced synthesis of enzymes or oxidative inactivation of protein enzymes 22 . Our findings in this study were in agreement with other studies, which revealed that cadmium induced kidney toxicity by enhancing ROS formation, GSH consumption, and inhibiting antioxidant-mediated defense system 34 . However, this study also suggested that the pre-administration of RJ prior to cadmium injection prevented the alteration in enzymatic and non-enzymatic activity of antioxidant molecules, and the antioxidant and metal-chelating properties of RJ also prevented the generation of free radicals, further reducing the cadmium-induced oxidative damage.…”
Section: Discussionsupporting
confidence: 93%
“…If the challenge is overcome, cells function and proliferation will recover and restart, but the preceding stress would accelerate cell senescence through multiple factors . In addition, intercellular components such as collagenous fiber would be increase in the process . In our biological detection, immunofluorescence staining showed that Cd induced p53 and p21 expression in mice kidney (Figure C,D), which were related with cell apoptosis.…”
Section: Discussionmentioning
confidence: 69%
“…In our previous research, Cd interferes mitochondrial metabolism and induces ROS generation, which results energy deficiency and oxidative stress of the cells, and causes the DNA damage . Protein p53 and p21 involved in regulation of cell apoptosis, necrosis and senescence via multiple signal pathway in the process .…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al reported that Potentilla anserina polysaccharide remarkably improved redox homeostasis in Cd-induced mice. It attenuated the mitochondria dysfunction, degeneration, and fibrosis of the kidney and exhibited anti-apoptosis activity via regulating both mitochondria-mediated intrinsic apoptotic pathway and the death receptor-initiated extrinsic pathway (Shen et al 2017). Chiu et al revealed that pretreatment of Cordyceps sobolifera polysaccharide improved LPS-induced kidney abnormalities and protected against LPS-triggered oxidative stress and inflammatory response (Chiu et al 2014).…”
Section: Other Renal Injury Rat Modelsmentioning
confidence: 99%